The effect of the health poverty alleviation project on financial risk protection for rural residents: evidence from Chishui City, China - Chu Chen; Jay Pan (BMC, 2019)
Abstract Background Illness is the leading cause (44%) of poverty in China. Since 2016, The health poverty alleviation project, an integral component of the Targeted Poverty Alleviation in China, was implemented in 2016 to strengthen financial risk protection against illness for financially backward segments of the population. However, the effects of the health poverty alleviation project on financial risk protection have not been explored in the literature, this paper aims to bridge the gap. Methods Using panel data on 63,426 rural households in Chishui City, China, from 2014 to 2017, the difference-in-differences with propensity score matching method was employed. Results The health poverty alleviation project reduces out-of-pocket payments by 15% on average and decreases the probability of catastrophic health expenditure (annual out-of-pocket payments exceeding 10% of annual household income) and impoverishing health spending occurrence (out-of-pocket payments are forcing a household into poverty or into deeper poverty) by 7.7 and 11.7%, respectively. Additionally, the project increases the number of annual hospitalizations per household by 0.035. Conclusion Our study demonstrates that the health poverty alleviation project significantly improves financial risk protection by reducing out-of-pocket payments and decreasing the probability of incurring catastrophic or impoverishing levels of health expenditure. Our study has implications for the poverty reduction policies and reform of the Chinese health financing system.